Fatty Liver and Its Associated Factors among Breast Cancer Patients in Dharmais Cancer Hospital, Jakarta - Philip Waruna; Kardinah -; Joedo Prihartono; Noorwati Sutandyo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Background: Fatty liver is frequently found during ultrasound (US) examination of breast cancer patients. It is not known how the association between breast cancer and fatty liver. This study was aimed to obtaine the prevalence of fatty liver in breast cancer patients and its association with clinical characteristics of the patients.Method: This was a cross-sectional study in Dharmais Cancer Hospital, Jakarta. Study subjects were breast cancer patients who came between January 2011 and December 2013. Fatty liver was assessed by using abdominal US and were grouped into mild, moderate, and severe. Clinical characteristics of the patients included age, body mass index (BMI), menopausal status, breast tissue density using Breast Imaging Reporting and Data System (BI-RADS), and immunohistochemical estrogen receptor (ER) status.Results: A total of 72 patients were enrolled during the study period with the mean age of 47.5 years. Fatty liver was found in 68 (94.4%) patients. Sixty (83.3%) patients had moderate-to-severe fatty liver. Patients with moderate-to-severe fatty liver had significantly higher BMI (26.9 ± 5.39 vs. 23.6 ± 4.05 kg/m2; p = 0.005). Fatty liver was not associated with the patient’s age, menopausal status, and breast tissue density.Conclusion: This study showed that the prevalence of fatty liver in breast cancer patients is very high. Fatty liver shows significant association with obesity but is not associated with breast tissue density or estrogen receptor status. Keywords: breast cancer, breast cancer density, fatty liver, estrogen receptor